2023
DOI: 10.1590/1414-431x2023e12728
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of mortality in critically ill patients with COVID-19 and diabetes

Abstract: The COVID-19 pandemic has challenged the entire world, and patients with diabetes mellitus (DM) have been particularly affected. We aimed to evaluate predictors of mortality during the first 30 days of hospitalization in critically ill patients with COVID-19 and comorbid DM. This prospective study included 110 critically ill patients admitted with COVID-19 infection. Thirty-two (29%) patients had a previous diagnosis of DM. Clinical variables, laboratory tests, and vascular biomarkers, such as VCAM-1, syndecan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Also, in the Gouzi et al survey, the Ang-2/Ang-1 ratio is a potential marker of vascular impairment in chronic obstructive pulmonary disease (COPD) patients. Moreover, according to the findings of Fang et al, Angiopoietin-2/Angiopoietin-1 and ratios could have a predictive value for early sepsis in an emergency department [31].In the study of Lázaro et al, the Ang2/Ang1 ratio was shown to be a predictor of severity among critically ill patients [33]. According to our research, the Ang-2/Ang-1 ratio is a potent severity indicator considerably higher in the critical group of COVID-19 patients, consistent with the findings of Abou-Arab et al research.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Also, in the Gouzi et al survey, the Ang-2/Ang-1 ratio is a potential marker of vascular impairment in chronic obstructive pulmonary disease (COPD) patients. Moreover, according to the findings of Fang et al, Angiopoietin-2/Angiopoietin-1 and ratios could have a predictive value for early sepsis in an emergency department [31].In the study of Lázaro et al, the Ang2/Ang1 ratio was shown to be a predictor of severity among critically ill patients [33]. According to our research, the Ang-2/Ang-1 ratio is a potent severity indicator considerably higher in the critical group of COVID-19 patients, consistent with the findings of Abou-Arab et al research.…”
Section: Discussionmentioning
confidence: 95%
“…Different conditions such as diabetes mellitus, atherosclerosis, hypertension, endothelial dysfunction, and impaired angiogenesis contribute to microvascular dysfunction [11], [19]. It has been demonstrated that markers of endothelial dysfunction and angiogenesis markers have been predictors of disease severity in heart failure, renal failure, and after cardiac surgery [20], [21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In parallel, increased serum levels of VCAM-1 were described in COVID-19 patients with distinct severity under dexamethasone treatment in correlation with classic sepsis biomarkers soluble urokinase-type plasminogen activator receptor and presepsin [ 52 ]. Recently, Lázaro et al proved that an even more augmented concentration of VCAM-1, with a high acute-lung-injury-specific angiopoeitin-2/angiopoietin-1 ratio, predicted unfavourable outcomes with a good efficacy in critically ill COVID-19 patients with diabetes mellitus [ 53 ]. In our current study, serum VCAM-1 showed a significant elevation in both survivors and non-survivors vs. controls and effectively distinguished these two COVID-19 subgroups from each other.…”
Section: Discussionmentioning
confidence: 99%